Personality traits in established schizophrenia: aspects of usability and differences between patients and controls using the Swedish universities Scales of Personality. (17th August 2016) - Fagerberg, Tomas; Söderman, Erik; Gustavsson, J. Petter; Agartz, Ingrid; Jönsson, Erik G.
Abstract: Background: Personality is considered as an important aspect that can affect symptoms and social function in persons with schizophrenia. The personality questionnaire Swedish universities Scales of Personality (SSP) has not previously been used in psychotic disorder. Aims: To investigate if SSP has a similar internal consistency and factor structure in a psychosis population as among healthy controls and if patients with psychotic disorders differ from non-psychotic individuals in their responses to the SSP. Methods: Patients with psychotic disorders ( n  = 107) and healthy controls ( n  = 119) completed SSP. SSP scores were analyzed for internal consistency and case-control differences by Cronbach's alfa and multiple analysis of covariance, respectively. Results: Internal consistencies among patients were overall similar to that of controls. The patients scored significantly higher in seven (Somatic trait anxiety, Psychic trait anxiety, Stress susceptibility, Lack of assertiveness, Detachment, Embitterment, Mistrust) and lower in three (Physical trait aggression, Verbal trait aggression, Adventure seeking) of the 13 scales of the inventory. In three scales (Impulsiveness, Social desirability and Trait irritability) there was no significant difference between the scoring of patients and healthy controls. Conclusion: The reliability estimates suggest that SSP can be used by patients with psychotic disorders in stable remission. Patients score higher on neuroticism-related scales and lower on aggression-related scales than controls, which is in accordance with earlier studies where other personality inventories were used.